2022
DOI: 10.3390/nu14051002
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Biomarkers: A Journey through Extracellular Vesicles

Abstract: Extracellular vesicles (EVs) have been identified as active components in cellular communication, which are easily altered both morphologically and chemically by the cellular environment and metabolic state of the body. Due to this sensitivity to the conditions of the cellular microenvironment, EVs have been found to be associated with disease conditions, including those associated with obesity and undernutrition. The sensitivity that EVs show to changes in the cellular microenvironment could be a reflection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 99 publications
(127 reference statements)
0
9
0
Order By: Relevance
“…Figure A,B shows representative expanded i–t traces of resistive pulses corresponding to a liposome entering and leaving the nanopipet at −1.0 and +1.0 V, respectively. The asymmetric shape of the resistive pulse arises from the conical shape of the nanopipet and indicates the direction that the liposome is traveling when translocating through the orifice. ,,,, A resistive pulse corresponding to a liposome entering the nanopipet exhibits a sharp decrease in current at the leading edge of the pulse, indicating when the liposome first passes through the nanopipet orifice. The current gradually returns to the open-nanopipet baseline current as the liposome travels up into the conically shaped nanopipet and no longer blocks the orifice (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure A,B shows representative expanded i–t traces of resistive pulses corresponding to a liposome entering and leaving the nanopipet at −1.0 and +1.0 V, respectively. The asymmetric shape of the resistive pulse arises from the conical shape of the nanopipet and indicates the direction that the liposome is traveling when translocating through the orifice. ,,,, A resistive pulse corresponding to a liposome entering the nanopipet exhibits a sharp decrease in current at the leading edge of the pulse, indicating when the liposome first passes through the nanopipet orifice. The current gradually returns to the open-nanopipet baseline current as the liposome travels up into the conically shaped nanopipet and no longer blocks the orifice (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are small, cell-derived unilamellar liposomes that contain biomolecules in the interior of the liposome (e.g., DNA, RNA, proteins), in addition to membrane-bound proteins on their exterior . Recent studies suggest that the interior and surface contents of EVs are directly correlated with their physical size. Zhang et al proposed a correlation between the size of EVs derived from AsPC-1 human pancreatic cancer and MDA-MB-231-4175 human breast cancer cell lines and their contents consisting of surface proteins, lipids, DNA, and RNA . They reported diverse organ biodistribution patterns for cancer-derived EVs of different sizes in mouse models and proposed biological functions of the EVs based on vesicle content and location within the body .…”
mentioning
confidence: 99%
“…In the last decade, EVs have been studied due to their active role in cell communication (see Mendivil et al, 2022 [ 17 ]). EVs are microparticles released by all cells into the extracellular space; their release and content respond to the conditions of the cellular microenvironment [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adipocytes have the ability to release EVs and studies carried out in humans and mice have shown that obesity can alter the size and number of adipocyte-derived EVs, as well as the expression of molecules associated with these EVs, such as miRNAs 12 14 . In this sense miR-132, miR-26b, and miR-155 are associated with obesity, lipid metabolism, adipogenesis, macrophage infiltration, inflammation, and insulin secretion, among others 15 19 .…”
Section: Introductionmentioning
confidence: 99%